2014
DOI: 10.1210/jc.2014-1441
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Thyrotropin Within the Near-Normal Range Are Associated With Increased Triiodothyronine But Not Increased Thyroxine in the Pediatric Age Group

Abstract: Within the near-euthyroid range, increasing TSH levels are associated with increasing FT3 levels, without an increase in FT4. This provides in vivo support for TSH enhancing preferentially T3 production and/or secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 17 publications
8
35
0
Order By: Relevance
“…A retrospective analysis of a large community-based pediatric clinic population in Jerusalem, which included some subjects with subclinical hypothyroidism, found positive correlations between BMI and TSH, fT3, and fT3:fT4 ratios. Conversely, fT4 demonstrated a negative relation with BMI (27). Although the relations between thyroid hormones and BMI were significant only in children with obesity, higher TSH correlated with higher fT3 (but not fT4) levels, even in healthy-weight children (27).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…A retrospective analysis of a large community-based pediatric clinic population in Jerusalem, which included some subjects with subclinical hypothyroidism, found positive correlations between BMI and TSH, fT3, and fT3:fT4 ratios. Conversely, fT4 demonstrated a negative relation with BMI (27). Although the relations between thyroid hormones and BMI were significant only in children with obesity, higher TSH correlated with higher fT3 (but not fT4) levels, even in healthy-weight children (27).…”
Section: Discussionmentioning
confidence: 82%
“…Conversely, fT4 demonstrated a negative relation with BMI (27). Although the relations between thyroid hormones and BMI were significant only in children with obesity, higher TSH correlated with higher fT3 (but not fT4) levels, even in healthy-weight children (27). A retrospective review of U.S. children and adolescents confirmed an association with higher TSH values at or slightly above the normal reference range with obesity; the free thyroid hormone data were not sufficient for analysis (34).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In children, we recently reported that within the normal range, the free triiodothyronine (FT3)/free thyroxine (FT4) ratio increases as thyroid-stimulating hormone (TSH) levels increase (1). This effect may be caused by increased deiodination of thyroxine (T4) to triiodothyronine (T3) that has been shown to occur in the cells of the thyroid gland in vitro in response to TSH (2,3).…”
Section: Introductionmentioning
confidence: 99%